Tracking working status of HIV/AIDS-trained service providers by means of a training information monitoring system in Ethiopia - Nadew Mesrak; Abduljewad Yassir; Pfitzer Anne; Hiner Cynthia A; McNabb Marion E; Faltamo Petros; Anderson Jean (BMC, 2009)
Abstract Background The Federal Ministry of Health of Ethiopia is implementing an ambitious and rapid scale-up of health care services for the prevention, care and treatment of HIV/AIDS in public facilities. With support from the United States President's Emergency Plan for AIDS Relief, 38 830 service providers were trained, from early 2005 until December 2007, in HIV-related topics. Anecdotal evidence suggested high attrition rates of providers, but reliable quantitative data have been limited. Methods With that funding, Jhpiego supports a Training Information Monitoring System, which stores training information for all HIV/AIDS training events supported by the same funding source. Data forms were developed to capture information on providers' working status and were given to eight partners who collected data during routine site visits on individual providers about working status; if not working at the facility, date of and reason for leaving; and source of information. Results Data were collected on 1744 providers (59% males) in 53 hospitals and 45 health centres in 10 regional and administrative states. The project found that 32.6% of the providers were no longer at the site, 57.6% are still working on HIV/AIDS services at the same facility where they were trained and 10.4% are at the facility, but not providing HIV/AIDS services. Of the providers not at the facility, the two largest groups were those who had left for further study (27.6%) and those who had gone to another public facility (17.6%). Of all physicians trained, 49.2% had left the facility. Regional and cadre variation was found, for example Gambella had the highest percent of providers no longer at the site (53.7%) while Harari had the highest percentage of providers still working on HIV/AIDS (71.6%). Conclusion Overall, the project found that the information in the Training Information Monitoring System can be used to track the working status of trained providers. Data generated from the project are being shared with key stakeholders and used for planning and monitoring the workforce, and partners have agreed to continue collecting data. The attrition rates found in this project imply an increased need to continue to conduct in-service training for HIV/AIDS in the short term. For long-term solutions, retention strategies should be developed and implemented, and opportunities to accelerate the incorporation of HIV/AIDS training in pre-service institutions should be explored. Further study on reasons why providers leave sites and why providers are not working on HIV at the sites where they were trained, in addition to our project findings, can provide valuable data for development of national and regional strategies and retention schemes. Project findings suggest that the development of national and region-specific human resources for health strategy and policies could address important human resources issues found in the project.